2020
DOI: 10.1038/s41598-020-77223-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of smoking on male lower urinary tract symptoms (LUTS)

Abstract: Lower urinary tract symptoms (LUTS) are substantially prevalent and increase with age. Research on smoking as a risk factor for LUTS has been inconclusive. The present study examined the association between smoking habits and male LUTS in a population-based study using a web-based questionnaire. We firstly screened a total of 10,000 male participants who were selected according to the age distribution in the Japanese population in government data, in order to check smoking habits. We then performed a web-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
0
12
1
Order By: Relevance
“…Among the other demographic variable studied in the literature, we did not observe any significant association between POUR and smoking status, BMI or previous surgical history. Although tobacco use was purported to enhance the rate of endothelial sclerosis leading to higher incidence of bladder ischemia and lower urinary tract complications, [26][27][28] such an association was not supported by our meta-analysis. Based on our meta-analysis, three co-morbidities were significantly associated with increased incidence of POUR, namely BPH, DM and CAD.…”
Section: Discussioncontrasting
confidence: 58%
“…Among the other demographic variable studied in the literature, we did not observe any significant association between POUR and smoking status, BMI or previous surgical history. Although tobacco use was purported to enhance the rate of endothelial sclerosis leading to higher incidence of bladder ischemia and lower urinary tract complications, [26][27][28] such an association was not supported by our meta-analysis. Based on our meta-analysis, three co-morbidities were significantly associated with increased incidence of POUR, namely BPH, DM and CAD.…”
Section: Discussioncontrasting
confidence: 58%
“…Prior studies have reported conflicting results for the relationship between smoking and LUTS incidence and progression. Kawahara et al 7 studied Japanese men ( n = 9042) in a cross‐sectional population‐based study using a web‐based questionnaire using several metrics including IPSS. They evaluated the symptoms of 3545 nonsmokers, 3060 ex‐smokers, and 2437 current smokers and reported that current smokers and ex‐smokers had significantly higher IPSS total scores than nonsmokers (mean [SD]: 5.75 ± 7.02, 6.58 ± 6.96, 4.23 ± 6.33, respectively; all comparisons p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Studies reported that compared with nonsmokers, smokers have a higher risk of LUTS, no additional risk and potentially, even a lower risk. [6][7][8][9] Similarly, among men with LUTS, consistent patterns have not been observed for the relationship between smoking and LUTS progression. 8,10 Therefore, while it is well-established that smoking has a multitude of adverse health effects, its effect on the incidence and progression of LUTS and BPH remains unclear.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The onset of LUTS could be triggered by several factors, such as diet ( 5 ), exercise ( 6 , 7 ), metabolic syndrome ( 8 - 10 ), environmental temperature ( 11 ), and so on. It has also been shown that LUTS is related to smoking ( 12 ), sedentary habits ( 5 ), urinary retention ( 13 ), etc., all of which are experienced by the young outpatient physicians, particularly those who work long shifts, in tertiary hospitals. In addition, sleep disorders may aggravate the symptoms of LUTS ( 14 ).…”
Section: Introductionmentioning
confidence: 99%